Synthesis of 2-Substituted Benzimidazoles Catalyzed by FeCl3/Al2O3 Under Ultrasonic Irradiation - Chen, Guo-Feng; Dong, Xiao-Yun; Meng, Fan-Zhu; Chen, Bao-Hua; Li, Ji-Tai; Wang, Shu-Xiang; Bai, Guo-Yi (Letters in Organic Chemistry, 2011)
2-substituted benzimidazoles have been synthesized in a single pot from aromatic aldehydes and ophenylenediamine catalyzed by FeCl3/Al2O3 in DMF under ultrasonic irradiation and afforded good yields in a short period of time.
Keywords: ultrasonic